MicroRNA-146a and microRNA-146b expression and anti-inflammatory function in human airway smooth muscle - Comer, Brian S.; Camoretti-Mercado, Blanca; Kogut, Paul C.; Halayko, Andrew J.; Solway, Julian; Gerthoffer, William T. (American journal of physiology. Lung cellular and molecular physiology, 2014)
MicroRNA (miR)-146a and miR-146b are negative regulators of inflammatory gene expression in lung fibroblasts, epithelial cells, monocytes, and endothelial cells. The abundance of cyclooxygenase-2 (COX-2) and IL-1β is negatively regulated by the miR-146 family, suggesting miR-146a and/or miR-146b might modulate inflammatory mediator expression in airway smooth muscle thereby contributing to pathogenesis of asthma. To test this idea we compared miR-146a and miR-146b expression in human airway smooth muscle cells (hASMCs) from nonasthmatic and asthmatic subjects treated with cytomix (IL-1β, TNF-α, and IFNγ) and examined the miRNAs' effects on COX-2 and IL-1β expression. We found that cytomix treatment elevated miR-146a and miR-146b abundance. Induction with cytomix was greater than induction with individual cytokines, and asthmatic cells exhibited higher levels of miR-146a expression following cytomix treatment than nonasthmatic cells. Transfection of miR-146a or miR-146b mimics reduced COX-2 and IL-1β expression. A miR-146a inhibitor increased COX-2 and IL-1β expression, but a miR-146b inhibitor was ineffective. Repression of COX-2 and IL-1β expression by miR-146a correlated with reduced abundance of the RNA-binding protein human antigen R. These results demonstrate that miR-146a and miR-146b expression is inducible in hASMCs by proinflammatory cytokines and that miR-146a expression is greater in asthmatic cells. Both miR-146a and miR-146b can negatively regulate COX-2 and IL-1β expression at pharmacological levels, but loss-of-function studies showed that only miR-146a is an endogenous negative regulator in hASMCs. The results suggest miR-146 mimics may be an attractive candidate for further preclinical studies as an anti-inflammatory treatment of asthma.